Yield and Response of Bean Breeding Lines for Drought Tolerance to Field Diseases - Amongi, Winnyfred; Mukankusi, Clare Mugisha; Sebuliba, Sulaiman; Nakyanzi, Brenda; Naluwooza, Claire; Baguma, Gerald (Canadian Center of Science and Education, 2019)
Climate change has resulted in an increase in the intensity of droughts and rains, and higher temperatures which are adversely affecting crop production in Africa. It has also influenced the distribution and increased the occurrence of disease and pest epidemics. Common bean (Phaseolus vulgaris L.) is especially sensitive to these changes. Most released varieties are not well adapted to environmental extremes and extended periods of drought in particular has become a major constraint. In this study, 462 advanced breeding lines developed for drought tolerance were evaluated for yield, agronomic traits and disease response in two contrasting agro-ecologies, Kawanda in the Lake Victoria crescent and Kachwekano in the southwestern highlands. Analysis of variance indicated significant differences (P < 0.05) among lines for most variables and environments (P <0.001). Performance was better at Kachwekano than Kawanda with mean yields ranging from 928 to 2251 kg ha-1, and 698 to 2036 kg ha-1 respectively. Angular leafspot, common bacterial blight and rust diseases varied between locations, and among lines with no visible to sever symptoms. Based on Wricke’s ecovalence estimates for stability, SCN20, SCN13, SEN114, SEC40 and SEC35 expressed yield stability and superiority. Of the 462 lines, 6.3 % maintained >1500 kg ha-1, the minimum anticipated commercial yield of new varieties, in all the trials, both seasons and in each year; 5.0 % also maintained above average yields. The most outstanding (1629-3944 kg ha-1) were; DAB299, DAB291, DAB234, DAD34, DAB478, DAB487, DAB543, DAB231, SCN20, SCR66, SCR60, and SER335. These are recommended for development of new varieties.